Ferimentos faciais: relato de caso - Gaetti-Jardim, Ellen Cristina [UNESP]; Santiago Júnior, Joel Ferreira [UNESP]; Guastaldi, Fernando Pozzi Semeghini [UNESP]; Dias-Ribeiro, Eduardo; Shinohara, Elio Hitoshio [UNESP]; Garcia Júnior, Idelmo Rangel [UNESP]; Jardim Júnior, Elerson Gaetti [UNESP] (My University, 2010)
Facial injuries vary in their clinical characteristics and complexity, deserves an appropriate approach for each case, considering that the failures may result in aesthetic and functional changes that can be harmful both functionally and psychologically. Aspects such as exposure time of the injury, anesthesia, suture materials and tetanus prophylaxis are important factors. The objective is to present a case of extensive facial injuries in an automobile accident patient.

Os ferimentos faciais variam nas suas características clinicas e complexidade, merecendo uma abordagem adequada para cada caso, haja vista que os insucessos podem resultar em alterações estético-funcionais que podem ser prejudiciais tanto funcional como psicologicamente. Aspectos como tempo de exposição do ferimento, anestesia, fios de suturas e profilaxia antitetânica constituem fatores importante. O objetivo do trabalho é apresentar um caso clínico de extenso ferimento facial em paciente vítima de acidente automobilístico
Facial wounds: case report
Keywords: Face; Injuries; Suture; Face; Lesões; Sutura